2013
DOI: 10.3389/fphys.2013.00110
|View full text |Cite
|
Sign up to set email alerts
|

A role for haemolymph oxygen capacity in heat tolerance of eurythermal crabs

Abstract: Heat tolerance in aquatic ectotherms is constrained by a mismatch, occurring at high temperatures, between oxygen delivery and demand which compromises the maintenance of aerobic scope. The present study analyses how the wide thermal tolerance range of an eurythermal model species, the green crab Carcinus maenas is supported and limited by its ability to sustain efficient oxygen transport to tissues. Similar to other eurytherms, C. maenas sustains naturally occurring acute warming events through the integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 71 publications
5
49
0
Order By: Relevance
“…Consistent with our findings, a study on Murray cod (Maccullochella peelii peelii) from southeastern Australia revealed that a continual increase in AS with temperature (from 14 to 29°C) was accompanied by a consistent rise in heart rate scope (Clark et al, 2005). Recent research on a eurythermal crustacean, the green crab (Carcinus maenas), showed that cardiac output remained unaffected by acute heat stress as temperature was increased from 10 to 25°C at a rate of 1°C h −1 (Giomi and Pörtner, 2013). Taken together, these results from waterbreathers resemble those recently reported for the air-breathing and semi-terrestrial cane toad (Rhinella marina) (Seebacher and Franklin, 2011;Overgaard et al, 2012).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Consistent with our findings, a study on Murray cod (Maccullochella peelii peelii) from southeastern Australia revealed that a continual increase in AS with temperature (from 14 to 29°C) was accompanied by a consistent rise in heart rate scope (Clark et al, 2005). Recent research on a eurythermal crustacean, the green crab (Carcinus maenas), showed that cardiac output remained unaffected by acute heat stress as temperature was increased from 10 to 25°C at a rate of 1°C h −1 (Giomi and Pörtner, 2013). Taken together, these results from waterbreathers resemble those recently reported for the air-breathing and semi-terrestrial cane toad (Rhinella marina) (Seebacher and Franklin, 2011;Overgaard et al, 2012).…”
Section: Discussionsupporting
confidence: 73%
“…Frederich and Pörtner, 2000;Sartoris et al, 2003;Lannig et al, 2004;Steinhausen et al, 2008;Farrell, 2009;Pörtner, 2010;Clark et al, 2011;Giomi and Pörtner, 2013). However, more chronic thermal exposures are arguably more relevant from a climate change perspective, especially if examining species that do not naturally experience broad thermal ranges over small temporal scales.…”
Section: Discussionmentioning
confidence: 99%
“…The well‐known progressive lowering of the affinity of oxygen‐binding proteins with increasing temperatures could explain how eurytherm crustaceans maintain efficient oxygen delivery at high temperatures. This mechanism has been demonstrated for the green crab ( Carcinus maenas ), showing that during acute heating the progressive hypoxemia and the resultant hemolymph acidosis greatly facilitated the unloading of oxygen into tissues. Thus, organisms with a good oxyregulatory ability may better tolerate high temperatures.…”
Section: Balancing Oxygen Supply and Demand While Breathing Water Ormentioning
confidence: 91%
“…Arterial haemolymph was withdrawn with the pipette from a hole (0.2 mm width) previously drilled through the carapace, over the pericardial sinus following Frederich and Pörtner (). Similarly, venous blood was withdrawn from the sinus below the arthrodial membrane, at the base of the fourth or fifth pereiopod (Giomi and Pörtner ). At each measurement the pipette was changed and the sensor properly washed with sterile water.…”
Section: Methodsmentioning
confidence: 99%